(untitled) (Journal of Engineering, 2024)
The research introduces a new mathematical model for computing the position of points in space (X, Y, Z) by the intersection of inclined angles derived from the measured horizontal and vertical angles using spherical trigonometry principles with the aid of the conventional surveying instrument (Theodolite), The most probable value (m.p.v) of the position of a point should be computed by the method of ieast squares when the redundancy in observations exists and then it provides us with the precision indices for the computed coordinates.